Water Buffaloes: A Changing of life cycle amidst social changes - เล็กประเสริฐ, เสาวลักษณ์; แป้นเส้ง, พิมพ์ประภา; ปานรังษี, เสาวลักษณ์; ศรีสุวรรณ, สุนิษา; เหมโก, นุชจรี; ตั้นตระกูล, ตันติกร; บัวแก้ว, จุรีรัตน์ (Journal of Liberal Arts Prince of Songkla University, 2016)
The objective of this study was to investigate water buffaloes’ way of life that has changed with the socio–economic change in Tambon Ban Khao, Ranot District, Songkhla Province. The data of this qualitative study were collected through in–depth interviews with three groups of local people consisting of five people who raised water buffaloes, five people who had abandoned water buffalo raising, and a focus group discussion with three people. buffaloes, five people who had abandoned water buffalo raising, and a focus group discussion with three people. The study revealed that in the past, water buffaloes were raised for the purpose of agricultural labor for people in Ban Khao. The raisers let them out from the pen early in the morning to graze in the field of grass in the wetlands and herded them back in the evening. Later, buffaloes have been raised for sale as a way of making income and the raising method has, thus, been changed. Buffaloes are looked after from the time they are herded out from the pen in the early morning until they are herded back in the evening. This reflects that buffaloes are under better care and the raisers sell their buffaloes only when they need money. Buffaloes are sold through a middleman and each buffalo can be sold for 10,000 baht or more. The land invasion by capitalists to build commercially agricultural and industrial sources has been a major cause that reduces the number of water buffaloes raised in this area, and that also made some households to eventually stop raising water buffaloes. Furthermore, the number of water buffalo raisers is decreasing and buffalo raising may vanish in the near future. As can be seen, the way of life of buffaloes has been changed according to the socio-economic conditions that have also been changed, and it is possible that the younger generations may not see buffaloes grazing in the wetlands anymore.